Efficacy of pectin solution for preventing gastro-esophageal reflux events in patients with percutaneous endoscopic gastrostomy - Kinoshita, Yoshikazu; Furuta, Kenji; Sumikawa, Masuko; Katoh, Kyoko; Aimi, Masahito; Hirata, Toshiaki; Sanpei, Mari; Ishine, Junichi; Adachi, Kyoichi; Fukazawa, Kousuke; Katoh, Setsushi; Ohara, Shunji; et al. (Journal of Clinical Biochemistry and Nutrition, 2012)
The aim of this study was to determine the efficacy of pectin solution, which increases the viscosity of liquid nutrient, for prevention of gastro-esophageal reflux in comparison with half-solid nutrient. The subjects were 10 elderly patients undergoing percutaneous endoscopic gastrostomy feeding. Twenty-four-hour esophageal multichannel intraluminal impedance and pH testing was performed during intake of half-solid nutrient and a combination of pectin solution and liquid nutrient. During 4 h after delivery, there was no significant difference in the total number of gastro-esophageal reflux events between the feeding of the half-solid nutrient and the combination of pectin solution and liquid nutrient (5.7 ± 1.2 vs 5.3 ± 1.0/4 h). Acidic reflux after delivery of the half-solid nutrient was significantly more frequent than that after delivery of the combination of pectin solution and liquid nutrient (80.7% vs 60.4%, p = 0.018). The incidence of gastro-esophageal reflux reaching the upper portion of the esophagus tended to be higher during delivery of the half-solid nutrient than during delivery of the combination of pectin solution and liquid nutrient (47.4% vs 34.0%, p = 0.153). In conclusion, the usage of pectin solution combined with liquid nutrient is effective for preventing acidic gastro-esophageal reflux and gastro-esophageal reflux reaching the upper portion of the esophagus.